The Effect of Dipole Moment of Analytes on the Response of Phthalocyanine Thin Films - Ozdemir, Okan; Misirlioglu, Banu Sungu; Altindal, Ahmet (AMER INST PHYSICS, 2016)
The effects of dipole moment of the analyte molecules on the response characteristics of bis(pentafluorophenyl)methoxyl substituted phthalocyanine thin film are explored to understand the details of molecular interactions of analytes with the sensor surface which lead to charge depletion and the chemiresistive effect. The concentration dependence of dc conductivity is measured to investigate the adress the response of the Pc film. It was found that the speed of the response is dominated by the polarity of the analytes. Four kinetic models, the first-order equation, the Elovich model, the second-order equation and the Ritchie's equation were selected to follow the adsorption process. The rate constants, equilibrium capacities and related correlation coefficients for each kinetic model were calculated and discussed. The second-order equation was the best of the various kinetic models studied to describe the adsorption kinetic of VOC vapours on Pc film, as evidenced by the highest correlation coefficients.
Keywords: SENSING PROPERTIES; METALLOPHTHALOCYANINES; ADSORPTION; SO2; Physics